Co-microencapsulation of Ruellia tuberosa L. and Cosmos caudatus K. Extracts for Pharmaceutical Applications - Annisa, Choirin; Prasetyawan, Sasangka; Safitri, Anna (UI Scholars Hub, 2022)
This study aims to co-microencapsulate the Ruellia tuberosa L. and Cosmos caudatus K. extracts, with chitosan–sodium tripolyphosphate (Na-TPP) as coating material. α-Amylase inhibition and antioxidant assays were conducted to determine the potential of microcapsules used as antidiabetic agents. The microcapsules were manufactured under the influences of pH, Na-TPP concentration, and stirring time. The optimum microencapsulation conditions were selected based on the highest encapsulation efficiency. The optimum microencapsulation conditions were a pH of 4, Na-TPP concentration of 0.15% (w/v), and stirring time of 60 min. The microcapsules exhibited an IC50 (inhibitory concentration) value of 223.64 ± 0.81 µg/mL and an α-amylase inhibition and antioxidant activity of 104.05 ± 0.88 µg/mL. The test for the release of bioactive compounds from microcapsules was conducted in HCl pH 1.2 and phosphate buffer pH 7.4 for 30–120 min. Results showed that 5.99% and 58.96% of bioactive compounds were released at pH 1.2 and 7.4, respectively, in 120 min. The Fourier transform infrared spectra showed the P=O functional group vibrations from Na-TPP at 1,213.71 cm−1 and C–N stretching vibrations from chitosan at 1,155.23 cm−1. Characterization with scanning electron microscopy and particle size analysis indicated that the microcapsules were spherical and had a mean diameter of 132.08 µm. The current study demonstrated that co-microencapsulation is a promising multifaceted approach for the enhancement of the pharmaceutical applications of plant extract combinations